2013
DOI: 10.1177/1090198112473112
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Sex Among Low-Income African American Young Women

Abstract: African American young women exhibit higher risk for sexually transmitted infections, including HIV/AIDS, compared with European American women, and this is particularly true for African American women living in low-income contexts. We used rigorous qualitative methods, that is, domain analysis, including free listing (n = 20), similarity assessment (n = 25), and focus groups (four groups), to elicit self-described motivations for sex among low-income African American young women (19-22 years). Analyses reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…One's motivations for engaging in sexual activity, particularly those related to love and intimacy, can strongly affect contraceptive behaviors, especially nonuse (Bjelica, 2008). In a qualitative study with African American women, participants listed a variety of reasons people might engage in sex (e.g., love/feelings, for fun, curiosity, pressured, for money, for material things), and they linked lack of condom use most strongly with love and intimacy motivations (Deardorff, Suleiman, et al, 2013). In a U.S. focus group study with adult women, participants gave 146 reasons for having unprotected sex .…”
Section: Relationship Factors: Dyadic Influences and Partner Preferencesmentioning
confidence: 99%
“…One's motivations for engaging in sexual activity, particularly those related to love and intimacy, can strongly affect contraceptive behaviors, especially nonuse (Bjelica, 2008). In a qualitative study with African American women, participants listed a variety of reasons people might engage in sex (e.g., love/feelings, for fun, curiosity, pressured, for money, for material things), and they linked lack of condom use most strongly with love and intimacy motivations (Deardorff, Suleiman, et al, 2013). In a U.S. focus group study with adult women, participants gave 146 reasons for having unprotected sex .…”
Section: Relationship Factors: Dyadic Influences and Partner Preferencesmentioning
confidence: 99%
“…Many of the women who were HIV-infected described a willingness to make concessions in order to preserve their relationship with a male partner. The concept of trust, supported in prior studies (Deardorff et al 2013; Mallory 2008; Paranjape et al 2006; Smith 2015) emerged as an important factor in women’s decisions to forgo the use of condoms when engaging in sexual behaviours. Trust was described as assuming their partner would not expose them to an STI, trusting their partner’s assurance that he was not infected and forgoing condom use as a declaration of her trust within their relationship.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have investigated the motivations for sexual activity among African American women, particularly when engaging in concurrent sexual relationships (Deardorff et al 2013; Ludema et al 2015). These studies found that, while participants agreed that condom use was important when engaging in risky sexual activities (for money or material things), they were not motivated to consistently use condoms when engaging in casual sexual relationships with a ‘non-main’ partner, or indeed, to ever use condoms.…”
Section: Introductionmentioning
confidence: 99%